Specialized visual learning of facial signals of quality in the paper wasp, Polistes dominula. (30th September 2014) - Sheehan, Michael J.; Sholler, Dan; Tibbetts, Elizabeth A.
<x xml:space="preserve">Abstract</x> Some primates and one species of paper wasp recognize faces using specific processing strategies to extract individual identity information from conspecific faces. Explanations for the evolution of face specialization typically focus on the complexity associated with individual recognition because all currently identified species with face specialization use faces for individual recognition. In the present study, we show an independent evolution of face specialization in a paper wasp species with facial patterns that signal quality rather than individual identity. Quality signals are simpler to process than individual identity signals because quality signals do not require simultaneous integration across multiple stimuli or learning and memory. Therefore, the results of the present study suggest that the complexity of processing may not be the key factor favouring the evolution of specialization. Instead, the predictable location of socially important signals relative to other anatomical features may allow easy categorization of features, thereby favouring specialized visual processing. Given that visual quality signals are found in many taxa, specific‐processing mechanisms for social signals may be widespread. © 2014 The Linnean Society of London, Biological Journal of the Linnean Society, 2014, 113, 992–997.